Back-Navigation String Matching Algorithm (BSMA) - Daniel, M.; Adiela Samuel, R.; Oriji Ikechi, B. (Department of Computer Science Faculty of Applied Sciences University of Sri Jayewardenepura, 2018)
This research took a comparative analysis on string matching algorithms. The study focused on developing an efficient algorithm (Back-navigation String matching algorithm) which will be used for large documents. The algorithm whilst compared to the existing system introduced a pattern of search which was done backwardly, from the last character to the first. The existing system considered more number of shifts which was slow and has a bad character shift. The research aimed at developing an efficient string matching for large documents sorting. The research methodology adopted for this project research is the verification and validation methodology which perform its test in a reverse manner so the software developer can at each stage review its step. The proposed system was executed and produced a result which compared with the existing system was termed efficiency. The system introduces a faster means of searching which starts form the last character to the first. The developed system which is the efficient string matching algorithm was analyzed and displayed a faster means of searching documents and is termed efficient because of its computing speed of 2 milliseconds while the naïve algorithm which ran with the computing speed of 154 milliseconds for a total number of 5000 characters.
Keywords: Algorithm, Automation, Comparative, Methodology, Navigation, String Matching